Hakim Peradilan Agama: Refleksi Sistem Pengangkatan dan Pelaksana Kekuasaan Kehakiman di Indonesia - Arif Rahman; Sofyan; Mulham Jaki Asti (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2022)
The Religious Courts are law enforcement institutions in Indonesia that cannot be separated from the existence of judges as executor and organizer of judicial power. In essence, religious court judges are appointed as state officials, consciously attaching cumulative conditions as mandated in Article 13 of Law Number 50 of 2009 concerning Religious Courts. The position of judges in carrying out their duties, functions and roles must really be able to actualize and apply the noble values ​​contained in the precepts of Pancasila and the 1945 Constitution as the constitutional basis for receiving, examining, adjudicating, and completing attribution authority. and its main distribution within the religious courts. The logical consequence of judicial power which is the responsibility of judges in religious courts cannot be denied by various problems and challenges both internally including the status of judge appointments, the judicial system, education and knowledge of judges, morality, and the welfare of judges. As well as externally which includes community participation, independence of judges, and a supervisory system.